Increasing Entrepreneurial Intentions of Generation Z as an Economic Engine: The Use of Digital Tools in Education - Mavlutova, Inese; Spilbergs, Aivars; Lesinskis, Kristaps; Maditinos, Dimitrios (Ekonomika, 2025)
Entrepreneurship plays a crucial role in economic development due to its positive impact on employment, innovation, productivity, capital formation and economic growth. In the context of the United Nations Sustainable Development Goals, entrepreneurship education is undergoing digital transformation. Technological advances and the emergence of Generation Z in the education system have led to the use of various digital tools with elements of artificial intelligence in the education process. This paper examines the impact of digital tools in entrepreneurship education on the entrepreneurial intentions of Generation Z as a significant economic driver based on experiments conducted in different countries of the European Union. A systematic literature review has been carried out on digital transformation in entrepreneurship education and its role in increasing entrepreneurial intentions, as well as an insight into generational theories and a description of the behavioural and perceptual characteristics of Generation Z. In the empirical part, a statistical data analysis has been conducted based on the results of an experiment performed in selected countries of the European Union, in which, the digital tool KABADA for teaching entrepreneurship to Generation Z was tested among business and non-business students. The results of the study show a significant influence of the use of digital tools in the teaching process on the entrepreneurial intentions of Generation Z, thereby confirming the findings which support the effectiveness of digitization-based entrepreneurship education in promoting entrepreneurial intentions and thus making an important contribution to economic development.
Keywords: entrepreneurship education; entrepreneurial intention; digital tool KABADA; artificial intelligence; Generation Z; regional differences